Implementation of User Centered Design Method on e-Catalog Information System of UMKM in South Aceh Agency - Fardiansyah; Anhar Pulungan; Ridha Sitorus; Muharratul Mina Rizky (Jurnal Inotera, 2021)
The utilization of digital technology produces efficiency, effectiveness and accountability that can support the UMKM (Usaha Mikro, Kecil, Menengah) so that the Regional Government (PEMDA) in this case the Koperasi and UKM Office of South Aceh agency can contribute in providing services and education for UMKM which are expected to be able to improve productivity and profit of UMKM in their region. To using of the UCD (User Centered Design) model involves the user in the development process. This study focuses on the implementation of the use of the UCD development model after going through the evaluation process of the user context, analysis and design of solutions based on recommendations from users. Based on the evaluation results, it is known that the implementation of UCD method to the system have a good response from users.